Japanese EFL Students’ Perceptions of Native and Non-Native Teachers of English as a Motivational Factor - Matsumoto, Masanori (Journal of Modern Languages, 2017)
Japanese high-school and university students studying English as a foreign language (EFL) were investigated for their views of their teachers as a factor affecting motivation to study English. In a questionnaire survey, 201 students answered regarding native English teachers and 173 on non-native English teachers. The study attempted to find the students' self-reported level of motivation and their perceived level of teachers' motivation to teach them English. It further examined which one among four teacher-related factors; "personality", "teaching-related", "classroom behaviour" and "other factors", the students perceive as most strongly affecting their motivation; and if there are any significant differences in the students' perceptions of the four factors between native and non-native teachers of English. Independent sample t-test and Chi-square tests were used to analyse the collected data. The results showed some noteworthy differences in the students' views on teachers between native and non-native speakers of English.